2019
DOI: 10.3846/cs.2019.576
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Virtual Teams: Bridging the Gap Between Professional Wisdom and Scientific Insights

Abstract: Following the growing body of scientific literature dedicated to the effects of virtual tools and environments on creative processes, we were interested in examining how professional creativity facilitators perceive these technologies and the extent to which they might support their dissemination. To this end, we conducted a workshop with 19 professional facilitators in which they could experience creativity in a virtual environment. Their ratings of the potential impact of such tools on session facilitation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…These results are in line with a more recent study (Buisine & Guegan, 2019) that allowed independent or internal consultants (from various companies) specialized in group facilitation for collaborative creativity sessions to experience teamwork in a virtual environment (avatar manipulation, navigation in the environment, interaction with team members, idea generation and discussion through instant messaging). They were instructed to visit the four target virtual places, explore them, discuss the pros and cons of each environment and imagine what kind of creative session they could conduct there with what kind of customer.…”
Section: Perception and Acceptability Of Vr And Muves Amongst Profess...supporting
confidence: 91%
“…These results are in line with a more recent study (Buisine & Guegan, 2019) that allowed independent or internal consultants (from various companies) specialized in group facilitation for collaborative creativity sessions to experience teamwork in a virtual environment (avatar manipulation, navigation in the environment, interaction with team members, idea generation and discussion through instant messaging). They were instructed to visit the four target virtual places, explore them, discuss the pros and cons of each environment and imagine what kind of creative session they could conduct there with what kind of customer.…”
Section: Perception and Acceptability Of Vr And Muves Amongst Profess...supporting
confidence: 91%
“…Restricted, turbulent and mainly digital reality represent an interesting avenue for studying the meaning of silence in communication with reference to creativity and innovation. The digital environment can help discover the creative potential of individuals, but also to give meaning to remote teamwork (Buisine & Guegan, 2019). We would expect that results provided in the current study may differ in digital context.…”
Section: Limitations and Future Researchmentioning
confidence: 85%
“…Short et al (1976) have developed a robust framework regarding social connectivity and digital communication forms. In addition, many academics have also researched remote team collaboration, such as Aragon and Williams (2011), Buisine and Guegan (2019), Humala (2015), Nemiro (2004), Stubbs and Baghurst (2014).…”
Section: Through My Study I Wanted To Examine Serendipity In Digital ...mentioning
confidence: 99%
“…Along with knowledge sharing and team trust, extensive studies have examined remote team creative collaboration (Aragon & Williams, 2011;Buisine & Guegan, 2019;Humala, 2015;Nemiro, 2004;Stubbs & Baghurst, 2014). However, some studies have demonstrated that team creativity is reduced when collaborating remotely versus collocated (Aragon & Williams, 2011;Stubbs & Baghurst, 2014).…”
Section: Remote Work Collaboration and Video-conferencingmentioning
confidence: 99%